SHARING KNOWLEDGE TO PROMOTE ACTIVE PROTECTION. CASE STUDY: SASSANO, CILENTO NATIONAL PARK - Biancamano, Paolo Franco; Viola, Serena; Pinto, Maria Rita (BDC. Bollettino Del Centro Calza Bini, 2013)
The paper deals with strategies for built heritage protection, creating conditions of design synergy between citizens, users and administrators. Sharing the constructive knowledge is a prerequisite for tackling settlements’ vulnerability, contrasting the imbalance between public and private. The research takes as a case study the historic urban landscape of Sassano in theCilentoNational Park. Thirty years later the 80’s earthquake, built environments’ transformations are linked both to the lack of technical knowledge and to a misuse of public funding for reconstructing. The paper testifies the effort to reverse a trend aiming to erase the constructive identity of landscapes. Acquiring and disseminating architectural and technological knowledge opens the path to development scenarios, arising from the sharing of context-aware protective micro actions.